Refigured Painting : The German Image 1960-88. (New York : Solomon R. Guggenheim Museum, 1989)
Hödicke, K.H. ; Baselitz, Georg ; Penck, A.R. ; Polke, Sigmar ; Kiefer, Anselm
Refigured Painting : The German Image 1960-88, Solomon R. Guggenheim Museum, New York, February 11 - April 23, 1989
boek
Keywords: Duitsland